PERTANGGUNGJAWABAN DOKTER DAN RUMAH SAKIT AKIBAT TINDAKAN MEDIS YANG MERUGIKAN DALAM PERSPEKTIF UU No 44 Th 2009 TENTANG RUMAH SAKIT - Njoto, Haryanto (DiH: Jurnal Ilmu Hukum, 2011)
Technology improvements and globalization invokes people’s realization about their rights as patients in a hospital.  They begin to demand getting those rights and when unsatisfied,   they may sue their doctors and the hospital. These litigation cases will, in the end, increase doctor’s and hospital’s risks. Increased risk means increased cost. It is mentioned in the forty sixth clause of the Hospital Law (Undang-Undang Nomor 44 Tahun 2009 tentang Rumah Sakit) that the hospital bears the responsibility of the mistakes done by it’s health workers. This clause seems unfair in taking the side of erroneous health workers, including doctors, and may result in the decrease of doctor’s feeling of responsibility in their patients. Being a corporation, a hospital can not being punished and so the responsibility falls on it’s owner and management. This can be seen as a violation of the human rights law against the hospital owner and management. The yudicial implications of a doctor’s mistakes in the process of taking care of their patients must be seen from the ethical and the law aspect. Seen from the ethical aspect, a doctor has to fulfill many requirements as a doctor. Seen from the law aspect, a doctor’s mistakes has to fulfill the criminal law, the civil law, and the administrative law. Doctor-patient relationships are usually inspanningsverbintenis (expedient relationship). In order to be able to sue their doctor, a patient has to provide provable evidence about the presence of mistakes or negligences made by the doctor, not just the absence of cure. Doctor-patient-hospital relationship is a tripartit relationship based on agreements between the three parties. Each party is entitled to his rights and obligations. A harmonious relationship and good communication between hospital, doctor and patient plays an important role in the prevention of medical litigations againts doctors and hospitals. Practicing dokctors have to realize that they better apply good responsibility by obeying the rules stated in the professional ethics and the law, always strive to increase their service, and master the art of good communication. Hospitals need to apply optimal service as required by the law by applying programs such hospital accreditation and patient safety programs. Medical committee need to be empowered to carry out is’s tasks, especially in credentialing, recredentialing, medical audit, and enforcing medical professional discipline and good clinical governance.